Peran dan Strategi Eklesiologi dalam pembentukan Iman Kristen di tengah perubahan Sosial dan Budaya - Septania Adut; Royasefa Ketrin; Pebri Asaria; Sarmauli Sarmauli (Publisher STPKat, 2024)
Doctrine of the church in the context of ecclesiology, focusing on several important aspects. First, the definition of church doctrine is explained as the study of the identity, function, and role of the church as the body of Christ, emphasizing that the church is not merely a physical building, but a community of believers united in faith. Next, the history and development of the church are outlined, demonstrating how the church has adapted to various challenges and social changes, including the emergence of different denominations that contribute to the understanding of ecclesiology today. The discussion also highlights the importance of doctrine for the spiritual life of the congregation, where doctrine serves as a theological foundation that influences faith growth, the formation of Christian character, and provides relevant moral guidance. Additionally, this paper identifies the challenges faced by the church in the modern era, such as secularism, religious pluralism, and social change, which require the church to remain relevant and responsive to contemporary issues.